CUTTING PROPAGATION OF PATCHOULI WITH DIFFERENT NUMBER OF LEAVES AND TYPES OF CUTTINGS - GARBUIO, Caroline; BIASI, Luiz Antonio; KOWALSKI, Ana Paula de Jesus; SIGNOR, Diana; MACHADO, Eliana Márcia; DESCHAMPS, Cícero (Scientia Agraria, 2007)
Patchouli (Pogostemon cablin) belongs to Lamiaceae family and has great comercial interest due the essential oil production in leaves which is used mainly in the perfumary industry. The objective of this work was to evaluate the root formation of patchouli according to leaf and stem cutting positions. The plant material was obtained from Joinville (SC). Two experiments were carried out using a complete randomized design with five replications. The first experiment investigated the effect of leaves on stem cuttings (stems without leaves and with one and two leaves) obtained from medium region of the stems. The second experiment compared the effect of the region of the stem as a source of cuttings and the treatments included basal, medium and apical regions. The stems from apical and medium region had one pair of leaves and the stem from basal region had no leaves. After 30 days the experiment results were evaluated. Stem cuttings collected from the apical and medium regions of the stem showed no statistical difference of rooting percentage (93,7% and 83,7%, respectively) and the length of the three great roots of the cuttings (11,1 cm and 10,2 cm, respectively), being superior than the basal stem cuttings. The root number on cuttings decreased from apical (35,5) to basal (7,3) region. Stems cuttings with two leaves and with one leaf showed higher root percentage (71,7% and 51,7%, respectively) and stem formation (78,4% and 44,9%, respectively) than the basal stems without leaves. The root number on stems decreased from stem with two leaves (25,7) than with one leaf (15,6) and withou leaves (2,7). Based on the obtained results, it is recommended the use of stem cuttings from apical and medium regions containing two leaves.